2019
DOI: 10.21451/1984-3143-ar2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiological stage and season on infrared thermograms of different body areas of dairy cows raised under tropical conditions

Abstract: The objective of this study was to investigate the influence of season and pregnancy stage on the temperature of various body areas of Holstein cows using digital infrared thermography, an effective and non-invasive technique. The temperature was recorded at several areas of the body surface to determine the most reliable body area for measurement of rectal temperature in pregnant and non-pregnant animals. Holstein cows (n = 24) were divided into groups according to their physiological stage. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…In contrast, observe that in the rear quarters these areas cover 60% of the surface and 80% of the rear teats. The presence of higher temperatures in the caudal area of the mammary quarters coincides with observations in dairy bovines raised under tropical conditions (Deak et al 2019).…”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, observe that in the rear quarters these areas cover 60% of the surface and 80% of the rear teats. The presence of higher temperatures in the caudal area of the mammary quarters coincides with observations in dairy bovines raised under tropical conditions (Deak et al 2019).…”
Section: Figuresupporting
confidence: 85%
“…It is also important to consider that, at least in cattle, the surface temperature of the caudal region of the udder by IRT may differ on occasions, and generally be higher (by 0.2-0.9 °C) than lateral readings. Finally, the temperature of the lateral udder can vary significantly depending on the season of the year and the reproductive stage (Deak et al 2019).…”
Section: Health Of the Udder Of Dairy Buffaloesmentioning
confidence: 99%
“…The above brings us back to discussing the possible influence of environmental conditions and the season when birthing occurs. A study by Deak et al ( 117 ) reported the effect of season and the physiological state of several body areas in 24 Holstein cows evaluated in the rainy (October- March) and dry seasons (April- September). They observed that temperatures in the flanks, perineal area, and lateral udder were 1.1°C higher in the rainy season than in the dry season and that temperatures of the udder, perineal, and rectal regions differed in the reproductive phase.…”
Section: Use Of Infrared Thermography In Assessing Hypothermia In New...mentioning
confidence: 99%
“…Of these regions, forehead temperature was shown to have the greatest correlation with rectal temperature ( r 2 = 0.35). In another study aimed at determining the most reliable body area for measurement of rectal temperature in pregnant and non-pregnant cows, the strongest correlation was found using the thorax ( r 2 = 0.377) with the udder and the eyeball showing slightly weaker correlations ( r 2 = 0.357 and r 2 = 0.316 respectively) ( 77 ). Thermogram temperature was also shown to differ between seasons and reproductive phases.…”
Section: Resultsmentioning
confidence: 99%